Perspektif Para Peneliti Senior Tentang Penyusunan Latar Belakang Penelitian yang Baik - Mohamad Muspawi; Ahmad Hidayat; Anti Yosefa; Muhamad Fajar Ronansyah; M. Nurmawan (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
Some final year students experience difficulties in writing scientific papers which lie in the preparation of research backgrounds. The purpose of this research is to describe the steps and strategies in writing the research background. The research methodology used was descriptive qualitative by interviewing senior researchers from the Jambi University Postgraduate Program. The results of the study show that to start conducting research, the first step is to find and determine the problem to be studied. Second, supported by supporting theory. And third, determine the purpose and usefulness of the research . The problems encountered by the authors are the beginning of a series of scientific paper writing. The problem is a phenomenon that occurs in the environment to be studied and is a reality in the field that looks different from what is expected. The background is supported by supporting theories and the aims and benefits of the research. In writing scientific papers contained in the research background.